Pengaruh Kombinasi Pupuk Kandang Sapi dan Konsentrasi Pupuk Organik Briket terhadap Pertumbuhan dan Hasil Tanaman Marigold (Tagetes patula L.) Varietas Prancis Petite Orange . - Romadi, Putri Fathi; Muharam, Muharam; Sugiono, Darso (UNIVERSITAS LABUHANBATU, 2023)
Marigold (Tagetes patula L.) is an ornamental plant that has benefits in various sectors. The quantity of marigold flower production is related to the cultivation technique used. Soil conditions also affect the level of plant fertility. This can be overcome by means of fertilization. The aim of this study was to obtain a combination of doses of cow manure and bricket organic fertilizer concentration which gave the highest growth and yield of marigold plants (Tagetes patula L.) var French Petite Orange. The research was conducted at the Soursop Gardens of Casamora, City Parks and Forest Service, Ciganjur, Jagakarsa, DKI Jakarta in March - June 2023. The research method used was an experimental method with a Single Factor Randomized Block Design (RBD) consisting of 5 treatments repeated 5 time. The treatment consisted of A (0 ton/ha Cow Manure + 0 ml Organic Fertilizer Briquette) (control), B (15 ton/ha Cow Manure + 1.5 ml/liter of water Briquette Organic Fertilizer), C (20 ton/ha Manure Cattle + 1.5 ml/liter of water Organic Fertilizer Briquettes), D (15 tons/ha Cow Manure + 3 ml/liter of water Organic Fertilizer Briquettes), E (20 tons/ha Cow Manure + 3 ml/liter of Briquette Organic Fertilizer water ). The results showed that there was a significant effect of giving a combination of doses of cow manure and briquette organic fertilizer concentration in treatment E (20 tons/ha of cow manure + 3 ml/liter of water of briquette organic fertilizer) on flower diameter (32.49 mm), number of flowers (7.47), the number of branches (6.07) the yield of fresh weight of flowers (10.19 g), the yield of dry weight of flowers (3.74 grams), the yield of total fresh weight of plants (192.69 g), and the yield of dry weight total plant (54.55 g).Â